Postoperative Acupuncture is as Effective as Preoperative Acupuncture or Meloxicam in Dogs Undergoing Ovariohysterectomy: a Blind Randomized Study - Ana Carla Zago Basilio Ferro; Caroline Cannolas; Juliana Cristianini Reginato; Stelio Pacca Loureiro Luna (Medical Association of Pharmacopuncture Institute, 2022)
Background : Acupuncture has the same analgesic effect as non-steroidal antiinflammatory drugs and opioids. It is challenging to perform preoperative acupuncture in unmanageable animals, while the residual postoperative anesthetic effect facilitates the performance of acupuncture postoperatively. Objectives: To compare preoperative acupuncture or meloxicam versus postoperative acupuncture for postoperative analgesia after ovariohysterectomy. Methods : This is a horizontal prospective positive control blind randomized experimental study. Thirty-six dogs were randomly divided into three groups: GA (preemptive acupuncture), GPA (postoperative acupuncture), and GM (meloxicam 0.2 mg/kg IV preoperatively). After sedation with acepromazine (0.05 mg/kg IM), anesthesia was induced with propofol (5.3 ± 0.3 mg/kg) and maintained with isoflurane/O2. Fentanyl (2 μg/kg, IV) was administered immediately before surgery. Bilateral acupuncture was performed at acupoints Large intestine 4, Spleen 6, and Stomach 36 for 20 minutes, before (GA) or immediately after surgery (GPA). Pain was evaluated by an observer blind to the treatment using the Glasgow scale before and for 24 hours after ovariohysterectomy. Dogs with a score ≥ 6 received rescue analgesia with morphine (0.5 mg/kg IM). Nonparametric data were analyzed by the Kruskal-Wallis test, followed by Dunn's test and parametric data by ANOVA followed by Tukey's test. Results : Two GA and one GPA dogs received rescue analgesia once. Two GM dogs received rescue analgesia and one of those was treated again twice. There were no differences in the number of dogs receiving rescue analgesia between groups (p = 0.80). Conclusion : Postoperative acupuncture was as effective as preoperative acupuncture or meloxicam in female dogs undergoing ovariohysterectomy.